2012
DOI: 10.1108/19852511211273697
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and access to interest bearing debt

Abstract: Purpose -We extend the growing body of literature on the impact of corporate governance on debt contracting by examining if better governance is associated with access to interest bearing debt. We explore if no-debt companies have governance structures that are qualitatively different to debt companies within a market with distinct corporate finance structure such as Australia. Design/methodology/approach -The analysis is portioned into two stages. The first stage focuses on univariate analysis which includes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Dittmar et al (2003) found that in a country with poor protection of shareholder rights, the asymmetry of information and investment opportunities does not have a significant impact on cash holding behaviors. Aldamen and Duncan (2012) found a relationship between corporate governance and the level of debt financing. Firms with higher levels of corporate governance have higher leverage and lower cost of debt.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Dittmar et al (2003) found that in a country with poor protection of shareholder rights, the asymmetry of information and investment opportunities does not have a significant impact on cash holding behaviors. Aldamen and Duncan (2012) found a relationship between corporate governance and the level of debt financing. Firms with higher levels of corporate governance have higher leverage and lower cost of debt.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…This finding suggests that banks give greater importance to audited financial information when deciding the interest rate. Aldamen and Duncan (2012) investigated the relationship between corporate governance and whether or not companies are able to access interest bearing debt in Australia. They found that debt companies have better corporate governance suggesting that the likelihood of accessing interest bearing debt is related to governance level.…”
Section: Review Of Empirical Literature and Hypotheses Developmentmentioning
confidence: 99%
“…Companies that implement higher governance are more likely to access interest bearing debt. Here the core driver is that companies with no-debt have systematically lower governance than all other companies (Aldamen and Duncan, 2012). Nini et al (2012) provided evidence that creditors play an active role in the governance of corporations.…”
Section: Debtmentioning
confidence: 99%